2019
DOI: 10.5146/tjpath.2018.01458
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of resin-induced gastrointestinal damage: report of 15 cases and review of literature

Abstract: Objective: Medication resins such as Kayexalate and Sevelamer used in the setting of chronic kidney disease for the correction of hyperkalemia and hyperphosphatemia are associated with gastrointestinal mucosal injury. In this study we describe the clinico-pathological features of Resin-induced gastrointestinal mucosal injury highlighting the histo-morphological appearances and differential diagnoses. The aim of this study is to increase the awareness of pathologists and clinicians alike to an under-reported et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Two mechanisms seen in the literature that may increase risk of adverse events are preexisting loss of mucosal integrity and increased length of exposure ( 7 , 8 , 10 , 11 , 17 ). Chronic conditions contributing to intestinal hypoperfusion such as diabetes, chronic liver disease, and heart failure can also adversely affect mucosal integrity over time ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two mechanisms seen in the literature that may increase risk of adverse events are preexisting loss of mucosal integrity and increased length of exposure ( 7 , 8 , 10 , 11 , 17 ). Chronic conditions contributing to intestinal hypoperfusion such as diabetes, chronic liver disease, and heart failure can also adversely affect mucosal integrity over time ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the several existing case reports, few have reported evidence of postdiscontinuation healing as observed by repeat endoscopy ( 5 , 6 ), rather most make inferences based on improvement of symptoms or do not address resolution of symptoms at all. Other case series demonstrate GI damage in the setting of sevelamer use and positive histology findings but do not comment on length of sevelamer use before diagnosis or resolution following discontinuation ( 7 , 8 ). A large randomized trial is not reasonable to perform because of the risks that would be imposed on the study groups; thus the existing pool of data is restricted to anecdotal evidence and observational studies.…”
Section: Introductionmentioning
confidence: 97%
“…George, et al [18] reported 15 cases of resin associated GI injury, 8 of which were associated with sevelamer (patient age 45-77; 2 female, 6 male). All of the cases involved the lower GI tract; sevelamer crystals were associated with abnormal findings including ulcerations of the colon or anal canal, pancolitis, inflammatory polyps, or diverticulitis with perforation.…”
Section: Discussionmentioning
confidence: 99%
“…These resins exchange sodium for potassium (SPS), and calcium for potassium (CPS) in the large bowel. Several gastrointestinal (GI) mucosal injuries after their utilization have been reported, including GI bleeding, necrosis, perforation, and pseudotumor (1)(2)(3)(4). The SPS/CPS-induced mucosal injuries were identified as basophilic mosaic crystals in the epithelium.…”
Section: Introductionmentioning
confidence: 99%